The Effect of Unemployment on Economic Growth in Nigeria (American Journal of Applied Statistics and Economics, 2023)
This study investigates the trends and effects of unemployment on economic growth in Nigeria using secondary data from relevant institutions for analysis from 2010 to 2020. The Auto Regressive Distribution Lag (ARDL) bounds test methodology is utilized to determine the long run relationship between unemployment and economic growth. The empirical findings using the ARDL Model confirmed that there exists an inverse relationship between economic growth and unemployment, and that unemployment leads to increasing crime rates in both short and long run.